2023
DOI: 10.3389/fpsyt.2023.1145606
|View full text |Cite
|
Sign up to set email alerts
|

Association of burnout with depression in pharmacists: A network analysis

Abstract: BackgroundBurnout and depression have overlapping symptoms, but the extent of overlap remains unclear, and the complex relationship between burnout and depression in pharmacists is rarely explored.MethodsWe investigated burnout and depression in 1,322 frontline pharmacists, and explored the complex relationship between burnout and depression in those pharmacists using network analysis.ResultsNetwork analysis showed that there were 5 communities. A partial overlap was found between burnout and depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Community pharmacists were less aware of the available occupational health and wellbeing support services compared to hospital pharmacists. The report suggested that working under increasing workload and the resulting impact on mental health and wellbeing is becoming normalized,which is a considerable concern 29 because other studies reveal 30 , 31 a partial overlap exists between burnout and depressive symptoms mainly in the connection between emotional exhaustion and reduced professional efficacy and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists were less aware of the available occupational health and wellbeing support services compared to hospital pharmacists. The report suggested that working under increasing workload and the resulting impact on mental health and wellbeing is becoming normalized,which is a considerable concern 29 because other studies reveal 30 , 31 a partial overlap exists between burnout and depressive symptoms mainly in the connection between emotional exhaustion and reduced professional efficacy and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, our study identified the significant relationship between the symptoms of “Emptiness” (SDS18) and life satisfaction in the high-neuroticism group. “Emptiness” (SDS18) reflects whether the individual thinks “My life is meaningless” [ 89 ]. Similar to the findings of the current study, Ritchie et al [ 90 ] investigated the relationship between neuroticism, meaninglessness, subjective well-being, and self-concept clarity and results showed that meaninglessness was positively associated with neuroticism while it was negatively related to life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Network structure among educational professions demonstrated that suicidal thoughts was only associated with other symptoms of depression, but not with those of burnout [ 41 ]. Another study showed that the symptoms of “feel down-hearted” and “no hope for future” were target interventions to relieve mental disorders of pharmacists [ 42 ]. However, it was uncertain whether these findings could be generalized to ICU nurses.…”
Section: Introductionmentioning
confidence: 99%